Programmatic Aspects of Initiating Kidney Transplantation in Ethiopia. (August 2017) - Ahmed, Momina M.; Bekele, Mahteme; Abebe, Engida; Tadesse, Mekdim; Berhe, Tekleberhan; Redae, Berhane; Abebe, Zerihun; Tedla, Fasika; Abate, Mersema; Jayaram, Deepa; Pestana, Jose M.; Reid, Lynn; et al.
Abstract : Introduction: We describe the development, at St. Paul's Hospital Millennium Medical College (SPHMMC), of the first kidney transplant (TXP) program in Ethiopia. Methods: The following steps were undertaken: 1) passage of legislation governing live organ donation and transplantation 2) recruitment of a nephrologist to SPHMMC and establishment of a hemodialysis program 3) selection by the Democratic Republic of Ethiopia's Ministry of Health of SPHMMC as the first TXP program site 4) partnership with the University of Michigan (UM) TXP program 5) recruitment of Ethiopian surgical TXP fellows 6) upgrading diagnostic capabilities 7) refitting of an existing free-standing building as the TXP center 8) selection and training of nursing, social work and pharmacy staff, and 9) porcine surgical simulations. Results: The International Society of Nephrology sponsored fellowship training in South Africa of an Ethiopian internist who returned in 2012 to establish the SPHMMC Renal Service and Inpatient Hemodialysis Program. The hospital acquired modern imaging equipment and revamped its clinical laboratory. To limit contact between immunosuppressed TXP recipients and other patients in the main hospital, an adjacent freestanding building was refitted as the TXP center. This center has 2 operating rooms, 4 intensive care unit beds, 6 patient rooms, a dialysis unit, a clinical laboratory, a TXP pharmacy, and an outpatient TXP clinic. Although, members of the local TXP team travelled to TXP centers in Egypt, India and the United States for observation and to Brazil's Hospital do Rim for hands on experience, TXP surgical training principally occurs at SPHMMC under the supervision of UM surgical faculty. In September 2015, in collaboration with UM TXP surgeons, the first Ethiopian kidney TXPs were performed at SPHMMC. TXPs are scheduled at roughly monthly intervals, when a UM TXP surgeon and TXP nurse and a US or Indian TXP nephrologist travels to SPHMMC. In addition, a general nephrology fellowship program was launched in May 2016. As of March 2017, SPHMMC has performed 36 live-donor kidney TXPs with >90% patient and graft survival. Conclusion: Proficiency of the local team is improving rapidly, with the goal of a fully independent program by the end of 2018. Careful planning and forging of key partnerships has been critical to the success of the kidney TXP program at SPHMMC. This "training in place" model could be replicated in other developing nations.